Rodina / domácnost jako náboženská skupina v procesu transformace - Nešpor, Zdeněk R. (Lidé města, 2010)
The theoretical roots and practical side of family life, or, life in a shared household, respectively, is closely associated with culture and with religious values. The mutual associations of both of these quantities are both rather presupposed than the subject of sociological studies, as the spirit of the secular point of view assumes that the significance of religiosity is on the decline and that religions chiefly support the so-called traditional model(s) of family. This presumption is not without truth, but it definitely does not explain all forms of modern religiosity and spirituality. In the article, the author on one hand summarises the basic theoretical and historical resources for examining the mutual bonds between religion and family life, and, on the other hand, presents their transformation in the Czech Republic after 1989 through an analysis of the sociological research projects ISSP 1998 and 2008. Changes in attitudes and in behaviour in family issues are connected with more general processes of political, economic and socio-cultural transformation and religious changes; they are not, however, directly derived from one another. At the same time, the determinate factor is the family, respectively, the ever-more frequent common household, which leads to a sort of de-individualisation of religion and spirituality; these socio-religious bonds also influence other spheres of economic and social behaviour.